2001
DOI: 10.1002/bit.10134
|View full text |Cite
|
Sign up to set email alerts
|

Real‐time in situ monitoring of freely suspended and immobilized cell cultures based on mid‐infrared spectroscopic measurements

Abstract: Glucose and lactate profiles in Chinese hamster ovary cell cultures were accurately monitored in real time and in situ during three bioreactor batch cultures lasting 11,15, and 15 days performed within a 60-day period. Monitoring was accomplished using in situ-collected mid-infrared spectra analyzed with a priori one-time established partial least-squares regression models. The robustness of the technique was demonstrated by application of these models without modification after 2.3 years. Neither recalibratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
61
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(63 citation statements)
references
References 54 publications
2
61
0
Order By: Relevance
“…When calibration models from off-line-collected spectra are established at some time prior to the application of these models to on-line-collected spectra, instrumental variations may have occurred. In the case discussed by Rhiel et al (2002b), off-sets could be attributed to differences in instrument alignment. The observed off-sets, however, were constant throughout each complete culture.…”
Section: Calibration Adjustments For On-line Monitoringmentioning
confidence: 91%
See 3 more Smart Citations
“…When calibration models from off-line-collected spectra are established at some time prior to the application of these models to on-line-collected spectra, instrumental variations may have occurred. In the case discussed by Rhiel et al (2002b), off-sets could be attributed to differences in instrument alignment. The observed off-sets, however, were constant throughout each complete culture.…”
Section: Calibration Adjustments For On-line Monitoringmentioning
confidence: 91%
“…The observed off-sets, however, were constant throughout each complete culture. Rhiel et al (2002b) showed that subtraction of the initial on-line prediction off-set resulted in accurate concentration predictions throughout the culture progression. The present situation is similar in that calibration models were established a priori with off-line-collected spectra.…”
Section: Calibration Adjustments For On-line Monitoringmentioning
confidence: 97%
See 2 more Smart Citations
“…The efficiency of a bioprocess can be optimized if the growth and morphology of the microorganisms used are monitored inline continuously, that is in real time without any offline sampling (Camisard et al, 2002). There exist various direct and indirect methods for the online measurement of cell concentration which are described in the literature (Konstantinov et al, 1994;Marose et al, 1999;Rhiel et al, 2001;Sonnleitner et al, 1992).…”
Section: Introductionmentioning
confidence: 99%